Investigations on the efficiency of cardiac-gated methods for the acquisition of diffusion-weighted images. - Nunes, R; Jezzard, P; Clare, S (2005)
Diffusion-weighted images are inherently very sensitive to motion. Pulsatile motion of the brain can give rise to artifactual signal attenuation leading to over-estimation of the apparent diffusion coefficients, even with snapshot echo planar imaging. Such miscalculations can result in erroneous estimates of the principal diffusion directions. Cardiac gating can be performed to confine acquisition to the quiet portion of the cycle. Although effective, this approach leads to significantly longer acquisition times. On the other hand, it has been demonstrated that pulsatile motion is not significant in regions above the corpus callosum. To reduce acquisition times and improve the efficiency of whole brain cardiac-gated acquisitions, the upper slices of the brain can be imaged during systole, reserving diastole for those slices most affected by pulsatile motion. The merits and disadvantages of this optimized approach are investigated here, in comparison to a more standard gating method and to the non-gated approach.